PELAKSANAAN WEWENANG WAKIL BUPATI PADANG LAWAS PROVINSI SUMATERA UTARA MENURUT UU NO 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Harahap, Adrian Hadi Putra; Indra, Mexsasai; Deliana, Evi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
With the background of the occurrence of conflict and disunity between the RegionalHead and Deputy Regional Head in Padang Lawas Regency which originated from the tidsk theRegional Deputy Head is involved in the administration of government so that the writer isinterested in researching it.The research method used in this thesis is a sociological legal research that is classifiedin the category of observational research (observational research). With Padang Lawas Regencyas the research location, but the authors chose the Regional Head and Deputy Regional Headwho carry out governmental tasks in Padang Lawas Regency with consideration, while thepopulation in the study was the Regional Head and Deputy Regional Head who served in thePadang Lawas Regency 2019-2024 service period as well as other authorized officials such asAssistant for Government, Head of government, Head of Law. Because the entire population ispossible to be sampled, the authors conducted a total sampling method in this study. While thesource of data in research is primary data obtained from samples and research locations usinginterviews, field observations and secondary data through literature studies and other primarylegal materials.The results of this study are that the Implementation of the Authority of the DeputyRegional Head in Law Number 23 Year 2014 is not clearly regulated because it only explains thegeneral description of the tasks of the Regional Head and Deputy Regional Head, while theauthority of the Deputy Regional Head, is only a delegation and mandate from the RegionalHead whereas the implementation of the division of authority of the Regional Head and DeputyRegional Head in Padang Lawas Regency is not going well which has implications for theoccurrence of conflicts and divisions due to the weak legislation that governs the distribution ofthe authority of Regional Heads and Deputy Regional Heads, both in the form of Laws Law, PP,PERDA, the source of authority granted Law Number 23 year 2014 on Regional Government toDeputy Regional Heads is only mandate / delegation authority not attribution, weakconstitutional basis for the existence of Deputy Regional Heads in the Constitution and politicalagreements such as financial and financial resources PEMILUKADA.The author's suggestion, in order to realize the objectives of regional autonomy theauthors suggest to the Parliament as a UUD 1945 Constitution by clarifying the existence of theDeputy Regional Head in the structure of regional government in Indonesia and strengtheningthe duties and authorities of the Deputy Regional Head in the form of legislation so that it has aposition and authority the stronger one.Keywords : Authority – Deputy Region Head – Regional Goverment